2019
DOI: 10.31744/einstein_journal/2020ao4877
|View full text |Cite
|
Sign up to set email alerts
|

Factors associated with the use of potentially inappropriate medication by elderly patients prescribed at hospital discharge

Abstract: Objective To analyze the frequency of use of potentially inappropriate medication prescribed to elderly at hospital discharge from a public hospital, considering the Brazilian Consensus on Potentially Inappropriate Medication for Elderly, and to identify the associated factors.Methods Patients aged ≥60 years, admitted in clinical and geriatric units of a public hospital were invited to participate in the study. The information about the use of medicines was collected from the patient’s electronic record and th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
12
0
5

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(20 citation statements)
references
References 30 publications
1
12
0
5
Order By: Relevance
“…Interestingly, our results showed that female gender (compared to male gender) and length of stay were independently associated with a higher prevalence of PIMs and lower prevalence of PPOs. In previous studies, gender was inconsistently associated with PIMs [25,26,28]. However, in line with our findings, two studies indicated that females had a higher risk of having a PIM [29,30].…”
Section: Discussionsupporting
confidence: 90%
“…Interestingly, our results showed that female gender (compared to male gender) and length of stay were independently associated with a higher prevalence of PIMs and lower prevalence of PPOs. In previous studies, gender was inconsistently associated with PIMs [25,26,28]. However, in line with our findings, two studies indicated that females had a higher risk of having a PIM [29,30].…”
Section: Discussionsupporting
confidence: 90%
“…A study using Beers Criteria in Medicare beneficiaries identified that 24.2% of the old people used PIM 13 . In hospital discharge prescriptions, PIM was found in 59.1% of the old people by STOPP 15 and in 58.4% by BCPIM 12 .…”
Section: Discussionmentioning
confidence: 97%
“…The proportion of old people who use some PIM depends on the location studied and the tools used for analysis 11 , but about 20% to 65% of the old people use at least one PIM 5 . The evaluation of the discharge prescription of old people from a public hospital in Minas Gerais, Brazil, showed that 58% included some PIM 12 . The use of PIM is associated with the occurrence of adverse drug reactions (ADRs), hospitalizations and increased health costs 11,13,14 .…”
Section: Introductionmentioning
confidence: 99%
“…In general, all benzodiazepines increase the risk of cognitive loss, delirium, falls, leading to fractures 4 , which consequently lead to hospitalization, leading to clinical complications that lead to death. Other studies 1,22 identified benzodiazepines as the most used among the interviewed participants.…”
Section: Discussionmentioning
confidence: 97%
“…Although necessary, some medications have their use problems superior to their benefit and, in some cases, due to changes in pharmacokinetic and pharmacodynamic responses resulting from the physiology of the older person. Thus, some medications are considered inappropriate for this age group, either due to lack of evidence about therapeutic efficacy, whose risk is greater than the clinical benefits provided, while safer and more effective alternatives are available, or when the use of the medication may aggravate preexisting diseases 1 .…”
Section: Introductionmentioning
confidence: 99%